Measuring the total logistics costs at the macro level: A study of Indonesia - Sugeng Santoso; R. Nurhidayat; Gustofan Mahmud; Abdul Mujib Arijuddin (Logistics, 2021)
Background: Efforts made to calculate the logistics costs in Indonesia, at the macro level, are facing various problems, due to the fact that there have been no national agreements - to any models employed - to calculate those costs. Moreover, limited data and information due to the lack of use of such integrated information technology to reduce the information asymmetry on the logistics processes and activities have created some additional problems. Objective: This study is aimed at reviewing the measurement model, of the logistics costs used in Indonesia, at the macro level. Method: It provides a potential measurement approach proposed by several previous studies as an alternative option that may help develop the existing models by elaborating on their limitations. Results: The results of this study emphasize the recognition of the components of the logistics costs and the formulation of a more accurate, transparent, and comprehensive measurement framework to improve the standard used to assess the logistics costs. Conclusion: Thus, the calculation output of the logistics costs is expected to be able to provide stakeholders with reliable information to develop an efficient logistics system. Furthermore, logistics costs will be more controllable, allowing Indonesia to achieve such comparative advantages.
Keywords: 650; Indonesia; logistics costs measurement; macro logistics costs